PENGARUH PARTISIPASI, PENEKANAN ANGGARAN DAN ASIMETRI INFORMASI TERHADAP BUDGETARY SLACK - Tamar I. M Bire Kire; Herly M. Oematan (Universitas Nusa Cendana, 2019)
This study aims to examine the effect of participation, budget emphasis, and information asymmetry on budgetary slack at the University of Nusa Cendana. The analysis technique used is multiple linear regression analysis which is partially tested. The population in this study were all work units at the University of Nusa Cendana. The selection of samples using purposive sampling method. The results of the study showed that partially participation and information asymmetry have a negative but not significant effect on budgetary slack at Nusa Cendana University. While budget emphasis has a significant positive effect on budgetary slack at Nusa Cendana University.